1991
DOI: 10.1152/ajpheart.1991.261.6.h1979
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of K+ and Ca2+ channels in experimental cardiac failure

Abstract: To examine the status of ATP-sensitive K+ (K+ATP) channels and 1,4-dihydropyridine-sensitive Ca2+ (Ca2+DHP) channels during experimental cardiac failure, we have measured the radioligand binding properties of [3H]glyburide and [3H]PN 200 110, respectively, in tissue homogenates from the rat cardiac left ventricle, right ventricle, and brain 4 wk after myocardial infarction induced by left coronary artery ligation. The maximal values (Bmax) for [3H]glyburide and [3H]PN 200 110 binding were reduced by 39 and 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In contrast to most studies, in which I Ca(L) density is evaluated in a small number of cells, in the present investigation, by analyzing a larger number of cells, we confirmed that I Ca(L) density is indeed reduced ( Figure 1A) in postinfarction myocytes, in agreement with the reduction in DHP binding sites described in homogenates from infarcted rats (14,17,18).…”
Section: L-type Calcium Channelsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to most studies, in which I Ca(L) density is evaluated in a small number of cells, in the present investigation, by analyzing a larger number of cells, we confirmed that I Ca(L) density is indeed reduced ( Figure 1A) in postinfarction myocytes, in agreement with the reduction in DHP binding sites described in homogenates from infarcted rats (14,17,18).…”
Section: L-type Calcium Channelsupporting
confidence: 87%
“…On the other hand, dihydropyridine (DHP)-binding sites have always been shown to be reduced (14,17,18), even in a study in which I Ca(L) density was found to be maintained (14). The peak amplitude of [Ca 2+ ] i transients has been shown to be reduced (3,11,19) or maintained (5,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) and how chronic and intermittent therapy with nitroglycerin affected responsiveness, as measured by receptor density and vascular reactivity responses [28,29]. The ability to conduct such collaborative work aimed at addressing clinically relevant questions was an excellent learning experience, which proved immensely valuable as I subsequently entered the pharmaceutical industry.…”
Section: Ion Channels As Regulated Speciesmentioning
confidence: 99%
“…For example, a significant decrease in cardiac [~H]I,4-dihydropyridine binding sites has been reported in this rat model. Gopalakrishnan and coworkers [36] reported a 40% decrease in the density of [3H]PN200-110 binding sites in the myocardium of rats 4 weeks following ligation of the coronary artery. The decrease in L-type voltage-sensitive calcium channel density reported by these investigators was not specific to the left ventricle, since this study also reported decreases in [3H]PN200-110 binding sites in the brains from these animals.…”
Section: Laboratory Approachesmentioning
confidence: 99%